2011
DOI: 10.1159/000333003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Oxidative Stress and Cardiomyopathic Changes in Ovariectomized Rats

Abstract: Objectives: Menopause has a negative effect on cardiovascular functions. However, very little is known of the overall effect of menopause on the cardiac ultrastructure or the pathophysiological basis of this. Methods: A group of 12-week-old female Sprague Dawley rats were randomly allocated to healthy control (n = 6) and ovariectomy groups (n = 6). Twelve weeks after ovariectomy, the rats’ cardiac tissues were histopathologically analyzed for determination of oxidant and antioxidant enzymes [activities of cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 80 publications
1
9
0
4
Order By: Relevance
“…Similarly to our results, Chung et al demonstrated that long-term treatment with RAL significantly decreased the cardiac activity of MPO in OVX rat [40]. While OVX increases the inflammation processes, the elevated levels of inflammatory markers can be decreased with hormone replacement therapy [41]. Oxidative stress plays a critical pathophysiological role during aging and after OVX.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to our results, Chung et al demonstrated that long-term treatment with RAL significantly decreased the cardiac activity of MPO in OVX rat [40]. While OVX increases the inflammation processes, the elevated levels of inflammatory markers can be decreased with hormone replacement therapy [41]. Oxidative stress plays a critical pathophysiological role during aging and after OVX.…”
Section: Discussionsupporting
confidence: 89%
“…Estudos experimentais indicam haver efeito protetor dos estrogênios no índice de apoptose dos cardiomiócitos 6 . No entanto, ensaios clínicos não mostraram haver proteção cardíaca nos esquemas de reposição hormonal 16,17 .…”
Section: Discussionunclassified
“…Em nosso estudo a análise histomorfométrica, número e volume nuclear dos cardiomiócitos do grupo que recebeu isoflavona apresentou valores semelhantes aos do grupo Ovx; já os dados do grupo E2 apresentaram-se semelhantes aos do Grupo Controle, mostrando ação protetora do estradiol em relação aos cardiomiócitos. Esses dados encontram apoio em trabalhos que referem haver diminuição na percentagem de apoptose no miocárdio de ratas tratadas com estrogênios devido à diminuição do TNF-alfa, Fas ligante (Fas L), receptores da morte Fas (FAS), Fas-associado ao domínio de morte (FADD), das caspases 3 e 8 ativadas 6,9 . Alguns autores relatam ainda que a ovariectomia aumenta o índice de apoptose nos cardiomiócitos e induz alterações dos genes pró-apoptóticos Bcl-2 e Bax 9,24 .…”
Section: Glso Govx Gctrlunclassified
See 1 more Smart Citation
“…Tem sido descrito que a alteração na concentração de GSH causada pela ooforectomia é acompanhada pelo aumento da peroxidação lipídica, com elevada produção de malondialdeído, e ainda, que a peroxidação lipídica aumenta com a idade (ALVARADO et al, 2006;KIRAY et al, 2007;VIVEROS et al, 2007). Nossos resultados são compatíveis com a maioria dos estudos, que relataram um aumento na peroxidação lipídica e uma diminuição nos níveis de GSH após ovariectomia (AKSAKAL et al,2011). Semelhantemente, em um estudo com ratos machos velhos (28 meses), oito semanas de treinamento físico induziu um aumento de GSH e da razão GSH/GSSG, sugerindo um aumento da resistência ao estresse oxidativo (RADAK et al,2004).…”
unclassified